Strategies of systemic treatment in patients with metastatic prostate cancer - Mackiewicz, Jacek; Woźniak, Sebastian (Contemporary Oncology/Współczesna Onkologia, 2009)
Prostate cancer (PC) is one of the most common malignant tumours in men. PC morbidity and mortality are constantly increasing. Despite radical treatment some patients will develop metastatic disease, becoming hormone therapy resistant. Treatment results of hor-mone-refractory prostate cancer (HRPC) are unsatisfactory. To date, the FDA has registered three cytotoxic drugs in this indication (estramustine, mitoxantrone, docetaxel), from which docetaxel is the most effective. The therapeutic vaccine sipuleucel-T (Provenge) seems to be closest to market authorization. The presented results of recent phase III studies have shown that sipuleucel-T extends median overall survival in HRPC patients. Promising results of other phase II studies (including atrasentan or calcitriol with docetaxel) have not been confirmed in a subsequent phase of studies. Some expectations are linked with new biological drugs such as bevacizumab or GVAX. Their value, however, requires confirmation in ongoing large randomized phase III trials, for the results of which we still have to wait.